Pemberian Pelayanan Jasa Kepada Masyarakat: Desain Goa Maria Gereja St. Mikhael, Kampung Kweel, Merauke: Giving Service To The Community: The Design & Budget and Cost Plansof Maria Cave In St. Mikhael Church, Kweel Village, Merauke - Yashinta Irma Pratami Hematang; Yosehi Mekiuw (Fakultas Peternakan Universitas Papua, 2021)
ABSTRACT Prayer activities, specifically for Catholics, are carried out through the Virgin Mary at a certain pilgrimage area. The Catholic Church of St. Michael in Kweel Village has a problem in planning for the construction of Maria Cave. As a form of Higher Education Tri Dharma, activities are carried out to provide cave design services along with the preparation of Budget and Cost Plans (RAB). The methods of implementing the activities include site/site data collection, analysis, drafting of design concepts, drawings, and ending with the making of the RAB. The result of the activity is the design of a Maria Cave measuring 8 X 5 m without roofing with geometric shapes consisting of public and private zones with the concept of utility lighting and resulting in building cost calculation with a value of Rp. 42,900,000. Keywords: Pilgrimage; Orison; Catholic Christianity ABSTRAK Kegiatan-kegiatan doa secara khusus bagi umat katolik adalah dengan melalui perantara Bunda Maria, pada suatu kawasan ziarah. Gereja Katolik St. Mikhael di Kampung Kweel memiliki permasalahan dalam perencanaan pembangunan Goa Maria. Sebagai salah satu bentuk Tri Dharma Perguruan Tinggi, maka dilakukan kegiatan pemberian pelayanan jasa desain goa dan penyusunan Rencana Anggaran dan Biaya (RAB). Metode pelaksanaan kegiatan meliputi: pengumpulan data site/tapak, analisis, penyusunan konsep desain, drawing, dan diakhiri dengan pembuatan RAB. Hasil kegiatan adalah desain suatu bangunan Goa Maria berukuran 8 X 5 m tanpa pernanungan dengan bentuk geometris yang terdiri atas zona publik dan privat dengan konsep utilitas pencahayaan lampu dan juga menghasilkan perhitungan biaya pembangunan goa maria dengan nilai bangunan adalah Rp. 42.900.000. Kata kunci: Ziarah; Doa; Kristen Katolik